Achieving food and nutrition security under rapid transformation in China and India: A synthesis. Issue 4 (2nd November 2015) - Fan, Shenggen; Rue, Christopher
Abstract : Purpose: – The purpose of this paper is to set the stage for the proceeding articles with background of the impressive yet incomplete progress made in eliminating hunger and malnutrition in China and India. Design/methodology/approach: – The paper provides background of the progress and challenges to achieving food security and nutrition in China and India. It then highlights the lessons learned from this special issue, and concludes with remaining knowledge gaps. Findings: – The paper summarizes findings from each article in the special issue. Originality/value: – Comparing the experiences of these two countries is essential to share knowledge and accelerate progress in eliminating poverty, hunger, and malnutrition both within these countries and globally.